2012
DOI: 10.3109/07853890.2012.663927
|View full text |Cite
|
Sign up to set email alerts
|

Glial cell line-derived neurotrophic factor: Characterization of mammalian posttranslational modifications

Abstract: Posttranslational modifications of GDNF influence its stability, which may be critical for its clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 47 publications
2
22
0
Order By: Relevance
“…However, we do not anticipate that these changes will increase the proteolytic stability in vivo and hence this parameter was not measured in our experiments. .GDNFv is expressed in CHO cells and is glycosylated at one position N49 (data not shown), N49 mutations to remove glycosylation in mammalian expressed GDNF resulted in significant lower expression levels, consistent with the finding by Piccinini et al (2013) . It was also observed that full length unglycosylated E. coli produced GDNFwt has significantly higher hydrophobicity than GDNFv produced by mammalian expression (data not shown).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, we do not anticipate that these changes will increase the proteolytic stability in vivo and hence this parameter was not measured in our experiments. .GDNFv is expressed in CHO cells and is glycosylated at one position N49 (data not shown), N49 mutations to remove glycosylation in mammalian expressed GDNF resulted in significant lower expression levels, consistent with the finding by Piccinini et al (2013) . It was also observed that full length unglycosylated E. coli produced GDNFwt has significantly higher hydrophobicity than GDNFv produced by mammalian expression (data not shown).…”
Section: Discussionsupporting
confidence: 87%
“…As result of bacterial expression, the molecule has an additional N-terminal methionine and is unglycoslyated. Piccinini et al (2013) recently showed that GDNFwt purified from E. coli had poor stability compared to mammalian expressed GDNF. Since the drug may need to reside in a pump/catheter system at body temperature for many weeks to months during infusion to PD patients, we have conducted stability studies with GDNFwt and identified two major deamidation and isomerization sites, Asn38 and Asp95.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The production method can also be important for the activity and solubility of the protein. For example, GDNF produced in E.coli is non-glycosylated whereas GDNF produced in mammalian cells is glycosylated and more stable 70 . The advantages of protein delivery are that protein receptor mediated signaling is limited by its half-life and the administration techniques via pumps can be intermittent and easily terminated.…”
Section: Gdnf-and Cdnf/manf-families Of Neurotrophic Factors: Effectsmentioning
confidence: 99%
“…As a multifunctional protein, GDNF has the ability to induce cellular survival, proliferation, migration and differentiation (13). To date, the scope of GDNF applications has been greatly expanded and includes the treatment of Huntington’s disease, amyotrophic lateral sclerosis, chronic pain, depression and addiction, as well as the regeneration of the sciatic nerve (14). In view of its numerous applications, GDNF was selected as the target protein in the present study.…”
Section: Discussionmentioning
confidence: 99%